IRIG-106 CHAPTER 10 RECORDER WITH BUILT-IN DATA FILTERING MECHANISM - Berdugo, Albert (International Foundation for Telemetering, 2007)
ITC/USA 2007 Conference Proceedings / The Forty-Third Annual International Telemetering Conference and Technical Exhibition / October 22-25, 2007 / Riviera Hotel & Convention Center, Las Vegas, Nevada === Sixteen years ago, RCC added Chapter 8 to the IRIG-106 standard for the acquisition of 100% MIL-STD-1553 data from up to eight buses for recording and/or transmission. In the past 5 years, the RCC recording committee added Chapter 10 to the IRIG-106 standard for acquisition of 100% data from PCM, MIL-STD-1553 busses, Video, ARINC-429, Ethernet, IEEE-1394, and others. IRIG-106 Chapter 10 recorder suppliers have further developed customer-specific interfaces to meet additional customer needs. These needs have included unique radar and avionic bus interfaces such as F-16 Fibre Channel, F-35 Fibre Channel, F-22 FOTR, and others. IRIG-106 Chapter 8 and Chapter 10 have provided major challenges to the user community when the acquired avionics bus data included data that must be filtered and never leave the test platform via TM or recording media. The preferred method of filtering data to ensure that it is never recorded or transmitted is to do so at the interface level with the avionic busses. This paper describes the data filtering used on the F-22 Program for the MIL-STD-1553 buses and the FOTR bus as part of the IRIG-106 Chapter 10 Multiplexer/Recorder System. This filtering method blocks selected data at the interface level prior to being transferred over the system bus to the media(s). Additionally, the paper describes the configuration method for defining the data to be blocked and the report generated in order to allow for a second party to verify proper programming of the system.